(3CWhGb GdMeGeI aj Med GdUMGHI Ydi GdSdGeIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s ((3ehSi Hf GHQGgje GdHUQi GdeOfi s)
(3ChdgG (B:s
(3eSFdI GdeNJGQ SdGeI GMhGd GdUMGHI QVi Gddg Yfge ef GdcaQ hGdZTQ HeG hQO ef GdKfGA Ydjge ef Gddg hef QShdg s
(3BNQgG (B:s
(3aCeG Gdbhd HGdcaQ hGdaSb ade jDKQ ai MK GdUMGHI Yf GMO ef GcGHQ Ggd GdHjJ hGaGVdge ceG McjfGg hbQQfGg hgh eQhO Ydi fGbdg GfJgi Je s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs